Penerapan Sistem Keamanan Jaringan Menggunakan Random Port Knocking Berbasis Raspberry Pi yang Dikirim Melewati Telegram - Iga Revva Princiss Jeinever (Jurnal Jaringan Telekomunikasi, 2018)
Computer networks are basically not safe to access freely. Security gaps in the network can be seen by irresponsible people with various techniques. Opening a port for access carries a high risk of being attacked by an attacker. In this connection, network administrators are required to work more to be able to secure the computer network they manage. One form of network security that is often used by network administrators in server management is through remote login such as ports on telnet, SSH, etc. A port that is always open is a network security hole that can be used by people who are not responsible for logging into the server. Focusing on these problems, in this study, Random Port Knocking is the right way and can be used to increase network security. With Random Port Knocking, the port will be opened as needed, the port will automatically change when it fails to log in more than three times and IP will automatically be blocked and access will not continue so that attacks on the network can be avoided and network security stability can be further improved. The final result of this research shows that the method applied in this research makes server safe. Because port randomization and IP block make irresponsible parties try harder to penetrate firewall walls.